LncRNA APCDD1L-AS1 induces icotinib resistance by inhibition of EGFR autophagic degradation via the miR-1322/miR-1972/miR-324-3p-SIRT5 axis in lung adenocarcinoma - Jie Wu; Chunlei Zheng; Yizhe Wang; Zichang Yang; Ce Li; Wanxia Fang; Yue Jin; Kezuo Hou; Yang Cheng; Jianfei Qi; Xiujuan Qu; Yunpeng Liu; et al. (BMC, 2021)
Abstract Background Epidermal growth factor receptor-tyrosinase kinase inhibitor (EGFR-TKI) resistance is the major obstacle in the treatment of lung adenocarcinoma (LUAD) patients harboring EGFR-sensitive mutations. However, the long non-coding RNAs (lncRNAs) related to EGFR-TKIs resistance and their functional mechanisms are still largely unknown. This study aimed to investigate the role and regulatory mechanism of lncRNA APCDD1L-AS1 in icotinib resistance of lung cancer. Methods Molecular approaches including qRT-PCR, MTT assay, colony formation, RNA interference and cell transfection, RNA immunoprecipitation (RIP), dual luciferase reporter assay, RNA fluorescence in situ hybridization, TUNEL assay, flow cytometry, immunoblotting, xenograft model and transcriptome sequencing were used to investigate the mechanism of APCDD1L-AS1 in icotinib resistance. Results A novel lncRNA, APCDD1L-AS1 was identified as the most significantly upregulated lncRNA in icotinib-resistant LUAD cells by the transcriptome sequencing and differential lncRNA expression analysis. We found that APCDD1L-AS1 not only promoted icotinib resistance, but also upregulated the protein expression level of EGFR. Mechanistically, APCDD1L-AS1 promoted icotinib resistance and EGFR upregulation by sponging with miR-1322/miR-1972/miR-324-3p to remove the transcription inhibition of SIRT5. Furthermore, SIRT5 elevated EGFR expression and activation by inhibiting the autophagic degradation of EGFR, finally promoting icotinib resistance. Consistently, the autophagy initiator rapamycin could decrease EGFR levels and increase the sensitivity of icotinib-resistant LUAD cells to icotinib. Conclusion APCDD1L-AS1 could promote icotinib resistance by inhibiting autophagic degradation of EGFR via the miR-1322/miR-1972/miR-324-3p-SIRT5 axis. The combination of autophagy initiator and EGFR-TKIs might serve as a potential new strategy for overcoming EGFR-TKIs resistance in LUAD patients.